Current status and perspectives of integrated traditional Chinese and Western medicine therapy for pancreatitis - CUI Naiqiang (Linchuang Gandanbing Zazhi, 2017)
Integrated traditional Chinese and Western medicine therapy for pancreatitis has been used since the 1960s. According to the clinical manifestations and traditional Chinese medicine (TCM) syndrome differentiation of pancreatitis, pancreatitis was named “true heart pain with cold limbs caused by spleen disease”. Syndrome differentiation of acute pancreatitis and treatment with modified Dachaihu decoction achieved good clinical effects. After the 1990s, the research focus of pancreatitis research was shifted to severe acute pancreatitis (SAP). The clinical course of SAP was divided into three phases, and different therapeutic regimens were given. Clinical studies achieved good therapeutic effects in terms of cure rate and fatality rate. After 2000, integrated traditional Chinese and Western medicine therapy for chronic pancreatitis has been promoted systemically, and the cooperation between traditional Chinese medicine, endoscopic techniques, and operative treatment helps to significantly improve pain control, nutritional status, and incidence of complications.